2010
DOI: 10.1088/0022-3727/43/30/305202
|View full text |Cite
|
Sign up to set email alerts
|

Lateral confinement of laser ablation plasma in magnetic field

Abstract: Abstract. The expansion of copper laser produced plasma along a magnetic field was investigated with the aim of confining the lateral expansion of the plasma. Time-resolved optical imaging, time-and space-resolved optical emission spectroscopy and time-of-flight Langmuir ion probe measurements were used to study the plasma dynamics. Thin films of copper were deposited without, and with, the magnetic field. It was observed that the magnetic field gives rise to substantial confinement of the plasma, leading to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…The second is related with guiding effects along the field lines, which are expected to reduce lateral divergence of fast ions, as seen in the increasing in Faraday cup signals in the presence of the magnetic field shown in figure 10. The observed increase in the axial ion flux is also consistent with previous reports, 27 and also with an observed strong reduction in the off-axis flux when an axial magnetic field is applied, as reported elsewhere. 28 In this context, previous investigations show that at low laser intensities, ∼1 GW/cm 2 , as in this case, the dominant ion acceleration mechanism is gas-dynamical, as opposite to electrostatic, due to the high pressure gradients produced at the initial stages of laser plasma formation.…”
Section: Aip Advances 7 085002 (2017)supporting
confidence: 93%
See 1 more Smart Citation
“…The second is related with guiding effects along the field lines, which are expected to reduce lateral divergence of fast ions, as seen in the increasing in Faraday cup signals in the presence of the magnetic field shown in figure 10. The observed increase in the axial ion flux is also consistent with previous reports, 27 and also with an observed strong reduction in the off-axis flux when an axial magnetic field is applied, as reported elsewhere. 28 In this context, previous investigations show that at low laser intensities, ∼1 GW/cm 2 , as in this case, the dominant ion acceleration mechanism is gas-dynamical, as opposite to electrostatic, due to the high pressure gradients produced at the initial stages of laser plasma formation.…”
Section: Aip Advances 7 085002 (2017)supporting
confidence: 93%
“…This configuration can be achieved by using two parallel magnets, which generate a magnetic field which is either transverse [24][25][26] or parallel [27][28][29] to the axial direction of the expanding laser plasma plume. Harilal et al 24 reported on the plasma dynamics and optical emission of an Al laser-produced plasma propagating in an almost uniform transverse ∼0.6 T magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Kondo et al [5] observed the confinement effect generated by magnetic field on laser-induced plasma, which leads to increased total ion beam current and longer plasma duration. Similar confinement effects by magnetic field have also been reported by Pagano and Lunney [6] and by Lash et al [7]. Kumar et al [8,9] have studied the dynamics of laser-produced plasma in a magnetic field, and a large enhancement of the emission intensity has been reported.…”
Section: Introductionsupporting
confidence: 75%
“…Previous studies employing a LPP expanding into a transverse B field showed that conversion of the plasma thermal energy into kinetic energy, plume confinement, ion acceleration, emission enhancement, plasma instabilities, etc. (Neogi & Thareja, 1999;Rai et al, 2003;Harilal et al, 2004;2005a;2005b;Pagano & Lunney, 2010;Kumar et al, 2011a;2011b;Pandey & Thareja, 2011). A B-field is capable of providing such a control by influencing the dynamics, ionization, and optical properties of a LPP.…”
Section: Introductionmentioning
confidence: 99%